Pengaruh Model Pembelajaran Projek Basic Learning Terhadap Penguatan Profil Pelajar Pancasila Kelas IV Di SDN No 104254 Sidodadi Ramunia Tp. 2023/2024 - Eli Pujiwati; Nizmi Putri; Thessa Heryana (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
Thesis with the title "The Influence of the Based Learning Project Learning Model on Strengthening the Profile of Class IV Pancasila Students at SDN No. 104254 Sidodadi Ramunia Academic Year 2023/2024" by: Eli Pujiwat ID: 120107087. The background of this research is that as many as 50% of students have not been able to collaborate with friends and teachers. In implementing learning, students have not been able to discuss well, tend to be more passive when carrying out discussions. This shows the lack of dimensions of the Pancasila student profile, namely mutual cooperation, global diversity. As many as 25% of students pray before starting learning, there are still many students who don't mean it and students can't respect friends of different religions. Students also cannot respect their friends when giving an opinion, and students tend to prefer to make fun of their friends. This shows the lack of dimensions in the profile of Pancasila students who are faithful and devoted to God Almighty. More than 50% of students cannot do their own work, which makes students copy their friends' work. The type of research used is qualitative research with an experimental approach. Experimental research, data collection techniques are documentation and tests. The results of this research can be concluded that, (1) After conducting research on learning outcomes in the social studies subject material with the subtheme Gratitude for Diversity in the experimental class with the Project Based Learning model using the t test, an average score of 82.4 was obtained. (2) After conducting research on learning outcomes in the social studies subject material with the subtheme Gratitude for Diversity in the control class using conventional methods using the t test, an average score of 68.4 was obtained. (3) Judging from the results obtained by students when studying using project based and conventional learning methods, they are very different. There is a difference between the experimental class and the control class, namely, in the experimental class the average value was 82.4 and in the control class the average value was 68.4. In the experimental class and the control class, the difference in the average score was 14.0, which if calculated in percentage form shows that the difference in the average score in the experimental class and the control class was 16.9%, which means that the score in the experimental class was 16 higher. 9% of the control class. So there is an influence on the results in the Social Sciences Subject material, Subtheme Gratitude for the Diversity of students with the project based learning model in class IV SDN No. 104254 Sidodadi Ramunia. This is proven by testing the hypothesis with the t test in the experimental class (Project based learning), the result obtained is 0.000, this value is smaller than Sig.(2-failed) α = 0.05 (0.000 < 0.05). So Ha can be accepted and Ho is rejected. So it can be concluded that there is an influence of the project based learning model on the results in the social studies subject material with the subtheme Gratitude for Diversity of class IV students at SDN No 104254 Sidodadi Ramunia.